Understory vegetation supports more abundant and diverse butterfly communities in oil palm plantations - Reiss-Woolever, Valentine Joy; Advento, Andreas Dwi; Aryawan, Anak Agung Ketut; Caliman, Jean-Pierre; Foster, William A.; Naim, Mohammad; Pujianto,; Purnomo, Dedi; Soeprapto,; Suhardi,; Tarigan, Ribka Sionita; Wahyuningsih, Resti; et al. (Frontiers in Forests and Global Change, 2023)
The cultivation of oil palm, from which palm oil, the world's most widely traded vegetable oil, is processed, has had marked effects on ecosystems and native species across the tropics. While declines in biodiversity due to conversion to oil palm have been well recorded across plant and animal taxa, less work has been done to identify approaches to plantation management which will enable producers to satisfy growing global demand while limiting environmental damage.Through a large-scale understory management experiment, we investigated the long-and shortterm effects of varying vegetation management regimes on the abundance, richness, and diversity of day-flying Lepidoptera. Over the long term, the lowest levels of vegetation complexity resulted in significantly lower Lepidoptera abundance, species richness and evenness. Less intensive understory clearing resulted in healthier communities, with limited differences between removal by herbicide application or chemical-free removal. Over the short term, biodiversity was not directly affected by vegetation complexity, suggesting that manual removal of vegetation may be equally damaging to butterfly or moth communities as removal by intermediate levels of herbicide spraying. These findings substantiate calls to limit vegetation clearing and maintain habitat heterogeneity on both a local and landscape scale, while also suggesting that a hard 'no-spray' guideline may not be the only option to support butterfly friendly plantations.